Immunogenicity of the pentavalent rotavirus vaccine among infants in two developing countries in Asia, Bangladesh and Vietnam - Shin, Sunheang; Anh, Dang Duc; Zaman, K.; Yunus, M.; Mai, Le Thi Phuong; Thiem, Vu Dinh; Azim, Tasnim; Victor, John C.; Dallas, Michael J.; Steele, A. Duncan; Neuzil, Kathleen M.; Ciarlet, Max (Vaccine, 2012)
► The immunogenicity of the pentavalent rotavirus vaccine (PRV) was studied in a sub-cohort of a Phase III efficacy clinical trial conducted in Bangladesh and Vietnam. ► Three oral doses of PRV were immunogenic, with a ≥3-fold increase of serum IgA responses shown in 88% of the subjects in two GAVI-eligible Asian countries. ► Both the serum anti-rotavirus IgA and serum neutralizing antibody responses were higher among infants in Vietnam than in Bangladesh, similar to the pattern illustrated in the efficacy estimates between these two countries. ► While the immunogenicity results among Vietnamese children were comparable to those in Latin America and Europe, the immune responses among Bangladeshi children resemble more those in impoverished populations in Africa. We evaluated the immunogenicity of the pentavalent rotavirus vaccine (PRV) in two GAVI-eligible Asian countries, Bangladesh and Vietnam, nested in a larger randomized, double-blind, placebo-controlled efficacy trial conducted over a two-year period from 2007 through 2009. 2036 infants were randomly assigned, in a 1:1 ratio, to receive three oral doses of PRV or placebo approximately at 6, 10, and 14 weeks of age. Concomitant use of EPI vaccines, including oral poliovirus vaccine (OPV) and diphtheria-tetanus-whole cell pertussis (DTwP) vaccine, was encouraged in accordance to the local EPI schedule. A total of 303 infants were evaluated for immunogenicity and blood samples were collected before the first dose (pD1) and approximately 14 days following the third dose (PD3). The seroresponse rates (≥3-fold rise from pD1 to PD3) and geometric mean titers (GMTs) were measured for anti-rotavirus immunoglobulin A (IgA) and serum neutralizing antibody (SNA) to human rotavirus serotypes G1, G2, G3, G4, and P1A[8], respectively. Nearly 88% of the subjects showed a ≥3-fold increase in serum anti-rotavirus IgA response in the analysis of the two countries combined. When analyzed separately, the IgA response was lower in Bangladeshi children (78.1% [95% CI: 66.0, 87.5]) than in Vietnamese children (97.0% [95% CI: 89.6, 99.6]), with a PD3 GMT of 29.1 (units/mL) and 158.5 (units/mL), respectively. In the combined population, the SNA responses to the individual serotypes tested ranged from 10 (G3) to 50 (G1) percentage points lower than the responses shown in the developed countries. However, the SNA response to G3 in Vietnamese subjects was 37.3% (95% CI: 25.8, 50.0), which was similar to the G3 response rate in developed countries. Three oral doses of PRV were immunogenic in two GAVI-eligible Asian countries: Bangladesh and Vietnam. The GMTs of both the serum anti-rotavirus IgA and SNA responses were generally higher in Vietnamese than in Bangladeshi children. The SNA responses varied by individual serotypes and were lower than the results from developed countries. The clinical significance of these observations is not understood because an immune correlate of protection has not been established.